Prediction of the soaked cbr of fine-grained plastic Soils through machine learning algorithms - Verma, Gaurav (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Prediction of the soaked cbr; of fine-grained plastic; Soils through machine; learning algorithms